Localized actions of progesterone in hypothalamus involve oxytocin. - Schumacher, M (1989)
Two ovarian hormones, estradiol and progesterone, which facilitate mating behavior in the female rat by acting on the ventromedial nuclei (VMN) of the hypothalamus, induce changes in oxytocin receptor binding in this brain region. Estradiol induced a 4-fold increase in the oxytocin receptor binding of the VMN and surrounding area and increased the number and immunostaining of oxytocin fibers in an area lateral to the ventral VMN. Progesterone, in estrogen-primed rats, caused the induced oxytocin receptors to spread over the area containing the oxytocin fibers. Infusion of oxytocin into the ventromedial hypothalamus increased the display of lordosis behavior only in females primed with both estradiol benzoate and progesterone. Thus, the sequential actions of two ovarian hormones bring a neuropeptide and its receptors into register and enable the neuropeptide to exert behavioral effects.